What Google doesn't know. - Willis Pershey, Katherine (Christian Century, 2015)
The article discusses the relation of Internet use to privacy in light of the hacking and release of user data from the extramarital affair web service Ashley Madison Inc. Topics include social commentary on the data breach, spiritual aspects of the knowledge collected on the Internet, and the notion of the self in relation to God in light of online identities.